Unleashing the watchdogs: explaining congressional assertiveness in the politics of US military interventions - Böller, Florian; Müller, Marcus (European political science review, 2018)
This article contributes to a burgeoning literature on parliamentary war powers by investigating the case of the US Congress drawing on both International Relations (IR) research and traditional war powers studies. Applying a fuzzy-set qualitative comparative analysis and case study method, we examine the conditions shaping congressional assertiveness. The article shows that the lack of national security interests and divided government are important conditions for members of Congress to criticize presidential intervention policies. While previous US war powers studies focused on the influence of partisanship, this article holds that domestic as well as international factors influence congressional behavior. A short comparative case study of two US military interventions (Libya 2011, ISIS 2014-15) during the Obama presidency serves to illustrate the findings.